Improvement of rheological properties of Algeria crude oil by addition of extra-light crude oil and a surfactant agent - Djemiat Djamal Eddine; Abdelhamid Safri; Abdelbaki Benmounah (Université de M'sila, 2021)
Effect of surfactant and extra-light crude oil addition on the rheological behaviors of an Algeria crude oil in order to improving its flowability were studied at low temperature. These rheological properties include steady flow behavior, yield stress and viscoelastic behavior. An AR-2000 rheometer was employed in all of the rheological examination tests. Results show that Toluene and extra-light crude oil addition causes a strong reduction in viscosity, the yield stress and can effectively increase of crude oil transport capacity. The toluene addition gets its best flow capacity and lowest viscosity at 6%. The extra-light crude oil addition obtains its best flow capacity and lowest viscosity at 50%. The viscoelasticity character of the crude oil has indicate a significantly influence by the addition of Toluene and extra-light crude oil.
Keywords: additive; apparent viscosity; crude oil; viscoelasticity character; yield stress